2002
DOI: 10.1207/s15327957pspr0602_03
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Stability From Infancy to Adulthood: Meta-Analysis and Dynamic Modeling of Developmental Mechanisms

Abstract: A central tenet of attachment theory is that a person's attachment pattern in adulthood is a reflection of his or her attachment history—-beginning with the person's earliest attachment relationships. However, the precise way in which early representations might shape adult attachment patterns is ambiguous, and different perspectives on this issue have evolved in the literature. According to the prototype perspective, representations of early experiences are retained over time and continue to play an influenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
203
1
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(229 citation statements)
references
References 100 publications
11
203
1
14
Order By: Relevance
“…A child is securely attached when it has a mental representation of the attachment figure as available and responsive when needed as a source of protection, comfort or validation. Insecurely attached children experience caregivers who are either inconsistently available and responsive, or consistently unavailable and neglecting (Fraley, 2002).…”
Section: Attachmentmentioning
confidence: 99%
“…A child is securely attached when it has a mental representation of the attachment figure as available and responsive when needed as a source of protection, comfort or validation. Insecurely attached children experience caregivers who are either inconsistently available and responsive, or consistently unavailable and neglecting (Fraley, 2002).…”
Section: Attachmentmentioning
confidence: 99%
“…Attachment research has provided evidence that infant attachment insecurity can later translate into insecure attachment patterns in close relationships during adulthood (e.g. Fraley, 2002). Research on adult attachment further sustains that RF is associated to the way people consciously manage actual significant relationships.…”
mentioning
confidence: 99%
“…Importantly, research evidence suggests that attachment styles tend to be rather stable from infancy to adulthood [63], nevertheless some authors see them more prone to change, especially with the individual's conscious efforts such as through therapy and mindfulness [64]. Also across relationships, it has been shown that people hold multiple working models organised as a hierarchy [65].…”
Section: Deliberation and Attachment Stylesmentioning
confidence: 99%